Scaffolded reaching experiences encourage grasping activity in infants at high risk for autism - Libertus, Klaus; Landa, Rebecca J. (Frontiers in Psychology, 2014)
Recent findings suggest impaired motor skill development during infancy in children later diagnosed with Autism Spectrum Disorders (ASD). However, it remains unclear whether infants at high familial risk for ASD would benefit from early interventions targeting the motor domain. The current study investigated this issue by providing three-month-old infants at high familial risk for ASD with training experiences aimed at facilitating independent reaching. A group of 17 high-risk infants received two weeks of scaffolded reaching experiences using ‘sticky mittens’, and was compared to 72 low-risk infants experiencing the same or alternative training procedures. Results indicate that high-risk infants – just like low-risk infants – show an increase in grasping activity following ‘sticky mittens’ training. In contrast to low risk infants, evidence that motor training encouraged a preference for faces in high-risk infants was inconclusive.